Leadership for deeper learning - Richardson, Jayson; Bathon, Justin; McLeod, Scott (Routledge, 2021)
"This exciting book explores how leaders have implemented, sustained, and pushed innovative, deeper learning opportunities in their school settings. Across the United States and around the world, the concept of a 'school' is growing more action-oriented, performance-focused, digitally relevant, and democratically infused. In this book you'll hear from real schools and leaders about practices that are changing schools and leading to deeper learning experiences across seven categories of innovative practice-including vision, agency in learning, trust in teachers, openness to new ideas, over-communicating change, equity mindedness, and courage to live outside norms. Leadership for Deeper Learning looks at how school leaders change the status quo and create different learning environments for students and teachers. Rich in stories and strategies, this book will provide you with the ideas and tools to rethink and reignite learning for the future"--
Keywords: Educational leadership; Educational change; School improvement programs; Educational innovations